Amyloid fibrils act as a reservoir of soluble oligomers, the main culprits in protein deposition diseases. (14th September 2022) - Bigi, Alessandra; Cascella, Roberta; Chiti, Fabrizio; Cecchi, Cristina
Abstract: Amyloid fibril formation plays a central role in the pathogenesis of a number of neurodegenerative diseases, including Alzheimer and Parkinson diseases. Transient prefibrillar oligomers forming during the aggregation process, exhibiting a small size and a large hydrophobic surface, can aberrantly interact with a number of molecular targets on neurons, including the lipid bilayer of plasma membranes, resulting in a fatal outcome for the cells. By contrast, the mature fibrils, despite presenting generally a high hydrophobic surface, are endowed with a low diffusion rate and poorly penetrate the interior of the lipid bilayer. However, increasing evidence shows that both intracellular α‐synuclein fibrils, as well and as extracellular amyloid‐β and β2‐microglobulin fibrils, can release oligomers over time that quickly diffuse to reach the membrane of the neighboring cells. The persistent leakage of harmful oligomers from fibrils triggers an ongoing cascade of events resulting in a sustained injury to neurons and glia and also provides aggregates with the ability to cross biological membranes and diffuse between cells or cellular compartments. Abstract : Amyloid prefibrillar oligomers formed during the aggregation process, or released from mature fibrils and senile plaques/inclusions, are the main pathogenic species in protein misfolding diseases. They can quickly diffuse and aberrantly interact with a number of molecular targets on neurons and glia, resulting in a fatal outcome for the cells.